Finite Element-Based Simulation of Cooling Rate on the Material Properties of an Automobile Silent Block - Burak Öztürk; Fuat Kara (Advances in Materials Science and Engineering)
The aluminum silent block is the part that connects the front suspension mounting and the road wheels. These products are used in high-speed cars and are subject to high engineering stresses. Over time, fractures occur in the connection part of these products due to insufficient strength. These problems are related to production metallurgy, which led to the concept of this study. During mass production, these parts are manufactured using the aluminum extrusion method. In this study, a rapid cooling process using water was applied, with the aim of improving the mechanical properties of the connecting part exposed to high dynamic loads. Samples were taken from the regions of these products which differed in thickness and width, and microhardness and tensile tests were performed for each region. The effects of both the extrusion cooling rate and the regional flash cooling on the material properties were then characterized. As a result of the isothermal transformation, the grain size in the microstructure of the material had shrunk. According to the findings, in this type of production, an average increase in strength of 25% was observed in the parts of the material subjected to maximum stress. The stress and safety coefficient values were found using finite element analysis, and curves were then drawn showing the differences in the safety coefficient values from the different points. As a result of cooperation between university and industry, the material and mechanical properties of an automobile part were improved in this study. This research has shown that, in terms of the accuracy of the results, it is very important to consider the variations in different regions of the product when defining the mechanical properties of any material produced by applying casting, heat treatment, and plastic forming methods.